Insights into the personality of 193 German elite youth football players and potential implications for the development of motor performance and injury risk - Schulz, S. V. W.; Holzapfel, J.; Matits, L.; Schwarz, E.; Bizjak, D. A.; Jerg, A.; Kiefer, M.; Kirsten, J.; Henze, A.-S. (Frontiers in Sports and Active Living, 2026)
Introduction: Sport-specific performance in football is influenced not only by physical, technical, and tactical factors but also by psychological characteristics such as personality. Previous research suggests traits like extraversion and conscientiousness are positively associated with athletic outcomes. A deeper understanding of personality may allow for more individualized training and support, potentially enhancing both short-term performance and long-term development. The present study aimed firstly to describe the prevalence and distribution of personality dimensions according to Cloninger's biopsychosocial model, assessed with the Junior Temperament and Character Inventory (JTCI), in German elite youth football players, and secondly to explore potential associations of these dimensions with motor performance and injury risk.